Development and field test of the articulated mobile robot T2 Snake-4 for plant disaster prevention. (17th January 2020) - Tanaka, Motoyasu; Kon, Kazuyuki; Nakajima, Mizuki; Matsumoto, Nobutaka; Fukumura, Shinnosuke; Fukui, Kosuke; Sawabe, Hidemasa; Fujita, Masahiro; Tadakuma, Kenjiro
Abstract: In this work, we develop an articulated mobile robot that can move in narrow spaces, climb stairs, gather information, and operate valves for plant disaster prevention. The robot can adopt a tall position using a folding arm and gather information using sensors mounted on the arm. In addition, this paper presents a stair climbing method using a single backward wave. This method enables the robot to climb stairs that have a short tread. The developed robot system is tested in a field test at the World Robot Summit 2018, and the lessons learned in the field test are discussed. GRAPHICAL ABSTRACT: